ANALISA YURIDIS SENGKETA PAJAK PADA PENGADILAN TATA USAHA NEGARA TERHADAP SURAT KETETAPAN PAJAK STUDI KASUS PUTUSAN PENGADILAN NO 606 K/TUN/2022 - Maralus Samosir; Yusuf Gunawan (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
This research aims to determine the mechanisms and procedures for resolving tax disputes in the judicial system in Indonesia, specifically knowing the mechanisms for resolving tax disputes and the characteristics of tax dispute resolution carried out by taxpayers regarding tax assessment letters (SKP) issued by the Directorate General of Taxes (DJP). The formulation of the problem in this research is: How are tax disputes in the State Administrative Court? How is the analysis of juridical considerations regarding the State Administrative Decision Number 606 K/TUN/2022? The research method used in this research is normative legal research, namely a legal research method which in principle carries out research on legal rules in legislation (Positive law), literature studies, jurisprudence and doctrine carried out qualitatively. The results of this research are that considering the subject matter of the dispute, the responsibilities of administrative officials, and the scope of the law, that tax disputes have almost the same characteristics as administrative disputes. The difference is, a tax dispute is not just about opposing a tax decision, but also calculating the amount of tax in dispute. The resolution requires a special court, for this reason the Financial Court was formed which is a specialty of the State Administrative Court. Often there is a gap in jurisdiction between the two courts, even though each court has its own absolute jurisdiction. The limits of the authority of the Tax Court and PTUN in matters of tax opinion can be seen, when it concerns the magnitude of SKP losses and procedural errors in disputed cases, the supervisory authority rests with the Tax Court. Court, whereas cases involving the legitimacy of power, alleged abuse of office, and unlawful acts, the PTUN has the right to examine them. Consideration of the Supreme Court judges through Decision Number: 606 K/TUN/2022 Whereas based on Article 1 number 5 of Law Number 14 of 2002 concerning the Tax Court, the definition of a tax dispute is a dispute that arises in the field of taxation between the Taxpayer or Tax Insurer and the official who has the authority as a result of the issuance of a decision that can be submitted for an appeal or lawsuit to the Tax Court based on tax laws and regulations, including a lawsuit regarding the implementation of collection based on the Law on Tax Collection by Force Letter. Whereas Article 1 number 7 of Law Number 14 of 2002 concerning the Tax Court regulates that a lawsuit is a legal remedy that can be taken by a taxpayer or tax bearer regarding the implementation of tax collection or against a decision that can be filed a lawsuit based on the applicable tax laws and regulations. That the legal remedy for Tax Collection Letters (STP) and Tax Underpayment Assessment Letters (SKPKB) whose issuance does not comply with the procedures or procedures stipulated in the provisions of tax laws and regulations is to file a lawsuit only with the Tax Court. Keywords: Tax Disputes, Tax Court, Administrative Court